All Days 2009
DOI: 10.2118/124349-ms
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Well Completion Applications for Passive Inflow Control Devices

Abstract: The main horizontal well completion issues have been identified and addressed during the previous decades, resulting in wells with better performance, lower water production and higher recovery efficiencies. One of the most important issues has been inflow equalization, which is affected by reservoir heterogeneities and pressure losses in the completion (annulus and liner). Evaluations of the flow equalization, in sandstone and natural fracture reservoirs, along horizontal wells have shown the importance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…The PICD modeling techniques and applications are described by Garcia et al 4,6 . From the mechanical shutoff solution point of view there are two cases that should be considered:…”
Section: Picd With Sliding Sleeve Modelingmentioning
confidence: 99%
“…The PICD modeling techniques and applications are described by Garcia et al 4,6 . From the mechanical shutoff solution point of view there are two cases that should be considered:…”
Section: Picd With Sliding Sleeve Modelingmentioning
confidence: 99%
“…The PICD modeling techniques and applications are described by Garcia et al 4,6 . From the mechanical shutoff solution point of view there are two cases should be considered:…”
Section: Picd With Sliding Sleeve Modelingmentioning
confidence: 99%
“…Fernandes et al (2009) presented a simple analytical method to determine the application conditions of ICD. Garcia et al (2009) evaluated the water control ability and yield-increasing effect of ICD completion by reservoir simulation when ICD technologies were applied to reservoirs of various types, and they found that ICD completion showed a good adaptability. But mathematical methods were seldom used to evaluate ICD adaptability.…”
Section: Introductionmentioning
confidence: 99%